Prognostic Value of Lymphocyte-Activation Gene 3 (LAG3) in Cancer: A Meta-Analysis - Saleh, Ramy R.; Peinado, Paloma; Fuentes-Antrás, Jesús; Pérez-Segura, Pedro; Pandiella, Atanasio; Amir, Eitan; Ocaña, Alberto (Frontiers in Oncology, 2019)
Introduction: Therapeutic targeting of inhibitors of the immune response have reached the clinical setting. Inhibitors of the novel receptor LAG3, that negatively regulates T cell activation, are under investigation. Here we explore the presence and prognostic role of LAG3 in cancer. Methods: A systematic search of electronic databases identified publications exploring the effect of LAG3 on overall survival (OS) and (for early stage cancers) disease free survival (DFS). Hazard ratios (HR) were pooled in a meta-analysis using generic inverse-variance and random effects modeling. Subgroup analyses were conducted based on disease site or tumor type. Results: Fifteen studies met the inclusion criteria. LAG3 was associated with better overall survival (HR 0.81, 95% confidence interval (CI) 0.66 - 0.99; P = 0.04) with subgroup analysis showing no significant differences between disease-site subgroups. The beneficial effect of LAG3 on OS was of greater magnitude in early-stage malignancies (HR 0.73, 95% CI 0.60 - 0.88) than in the metastatic setting (HR 1.20, 95% CI 0.70-2.05), but this difference did not meet statistical significance (subgroup difference p = 0.18). LAG3 was not associated with a significant association with DFS (HR 1.02, 95% confidence interval (CI) 0.77-1.37; P = 0.87) with subgroup analysis showing worse DFS in patients with lymphoma and improved DFS in the breast cancer. Conclusions: High expression of LAG3 associates with favorable overall survival in several solid tumors. A trend for an association in early stage disease suggests the importance of immune surveillance in this setting.